IMPACT OF THE COVID-19 PANDEMICS AND SOCIAL ISOLATION ON BEHAVIOR AND MENTAL HEALT AMONG MEDICAL AND NON-MEDICAL STAFF – EXPERIENCE FROM A SINGLE OBSTETRICS AND GYNECOLOGY CLINIC - Aničić, Radomir; Rakić, Aleksandar; Sretenović, Dragutin; Kocić, Jovana; Štulić, Jelena; Ristić, Aleksandar; Dimitrijević, Dejan; Nejković, Lazar (Medical Research, 2023)
Introduction/Aim: Occupational exposure of health workers makes them vulnerable and at high-risk for COVID 19 infection and major psychological disturbances. Fear of the unknown, close family and friends, rapid exhaustion of personnel protection equipment, direct contact with infected patients, combined with the media-encouraged panic, create an immersive psychological burden for the healthcare workers. The aim of this study was to assess the mental health of the medical and non-medical staff at a single University Obstetrics and Gynecology Clinic during COVID-19 epidemic in Serbia.Methods: A study was conducted from 1st to 31st of May 2020 through 160 online questionnaires distributed among staff at single Obstetrics and Gynecology Clinic. This online survey consisted of two sections: one included questions related to demographic characteristics, medical history, habits during the COVID 19 pandemic, and coping mechanisms; the other comprised questions included in Depression, Anxiety and Stress Scale 21 (DASS-21).Results: Among 118 employees who have participated in the study, depression, anxiety, and stress were present in 35.6%, 40.7%, and 27.1% participants. Participants with lower education had higher total DASS, depression, anxiety, and stress scores compared to participants with higher education. Non-medical staff had significantly higher total DASS and anxiety scores than medical staff. Participants with lower education and married subjects were more likely to have anxiety and depression symptoms.Conclusion: Apart from the medical staff, non-medical personnel and their mental status should not be neglected, and we aim for future studies, regarding the psychological impact of public health emergencies, to include this group in their research.
Keywords: COVID 19; medical staff; non-medical staff; obstetrics and gynecology; psychological impact